Property between Natural and Acquired Right - Alsubuh, Riyad; Shomar , Towfic (Jordan Journal of Social Sciences, 2022)
The main objective of this study is to discuss the bases of why some philosophers assume that property is an essential part of human rights based on accepting it as a “natural” right, and to assess the credibility of such an assumption. In order to deal with such problematic issue, we contrast John Locke and Georg Hegel with Friedrich Engels; Locke posited that privet property right is part of natural rights, while Hegel claimed that privet property is a right granted by the state. In contrast, Engels thought that the origin of property, during the early stages of humanity, was that of communal or public property, which later changed to privet property due to the division of labour and the emergence of class societies and class straggle. The study draws a comparison between Hegel and Engels on several points: family, society, social contract, and the state. The study concluded that property, be it privet or public, is not a right but a means for a right, because it is based on the ability to be transferred and exchanged, whilst the natural right ought to be nun-transferable. The only right the state have is to put forward policies of property that would not inflect the natural origin of human rights.